(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the linguodidactic features of developing speech competence among academic lyceum students. The linguistic, communicative, discursive, pragmatic, and strategic components of speech competence are described as an interconnected system, and the methodological conditions for their development in the educational process are substantiated. Considering the age-related, intellectual, and communicative characteristics of academic lyceum students, the article explores the potential of text-based activities, problem-based questions, discussions, creative writing, oral presentations, and collaborative tasks. It also demonstrates the importance of linguodidactic principles, interactive methods, and the integration of different types of speech activity in developing students’ ability to express their ideas logically, coherently, convincingly, and appropriately in various communicative situations. The article proposes methodological recommendations aimed at enhancing speech competence in academic lyceum education.